Dynamic Modeling and Simulation of How Information Sharing Influences Supply Chain Performance - Weibin Wang; Renyong Chi (Discrete Dynamics in Nature and Society)
With the growing intensity of cooperation, the partners in the manufacturing supply chain (SC) raise stricter requirements for information sharing (IS) within the SC, which has been an effective capability to improve the performance of manufacturing SC. To reveal the influence of IS on SC performance, this paper firstly carries out a theoretical analysis on the influencing factors of IS, SC integration and SC performance, and builds a theoretical model of the IS’s impacting on SC performance. Next, valid index data were obtained by investigating typical manufacturing enterprises in Yangtze River Delta region of China. Then, according to the dynamics system flow of IS influence on SC performance, the proposed theoretical model would be modeled from system dynamics and simulated by Vensim PLE software. The results show that IS among manufacturing SC nodes enhances the SC performance via SC integration; when SC integration is suitable for IS, SC performance will be improved as long as the IS amount is greater than zero; however, excessive IS would reduce the quality and weaken the amount of IS; overall, the degree of IS and SC integration are the key to better SC performance. This implies that how to improve IS among SC partners is a very important thing in manufacturing SC management. And, it also enlightens that enterprise managers should pay attention to establish a high-level trust relationship with SC partners, achieve high-quality IS with a wider range, and then promote the SC system more integrated to improve its operational performance.